Pengaruh Citra Merek dan Promosi Online terhadap Keputusan Pembelian (Survei pada Konsumen Triset di Tasikmalaya) - Siti Annisa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the simultaneous and partial effect of brand image and online promotion on purchasing decisions for Triset products in Tasikmalaya. The method used in this research is a survey method with a quantitative approach. The population studied were 100 respondents. The data collected in the form of primary data and secondary data. Data analysis in this study used multiple linear regression analysis using SPSS veris 24 software. The results showed that brand image and online promotion simultaneously had a significant effect on purchasing decisions for Triset products in Tasikmalaya. Brand Image partially has a significant effect on purchasing decisions for Triset products in Tasikmalaya. Online promotion partially has a significant effect on purchasing decisions for Triset products in Tasikmalaya.